Abdominal compartment syndrome – the prevention and treatment of possible lethal complications following hip arthroscopy: a case report - Ciemniewska-Gorzela, Kinga (J Med Case Rep, 2014)
INTRODUCTION: Intra-abdominal hypertension and abdominal compartment syndrome have been increasingly recognized as a hip arthroscopy complication over the past decade. In the absence of consensus definitions and treatment guidelines, the diagnosis and management of intra-abdominal hypertension and abdominal compartment syndrome remains variable from institution to institution. CASE PRESENTATION: We report the occurrence of the extravasation of fluid into the abdomen during arthroscopic treatment of femoroacetabular impingement combined with resection of trochanteric bursa and our management of the condition in a 55-year old Caucasian woman. CONCLUSIONS: We present an algorithm of treatment of abdominal compartment syndrome, as a hip arthroscopy complication, according to the consensus definitions and recommendations of the World Society of the Abdominal Compartment Syndrome. In the algorithm options, we have included paracentesis and percutaneous catheter decompression as the main point of treatment. Our algorithm will have a broader clinical impact on orthopedic surgery, anesthesiology and emergency medicine.